2023
DOI: 10.1111/acel.13826
|View full text |Cite
|
Sign up to set email alerts
|

Senescent cells enhance newt limb regeneration by promoting muscle dedifferentiation

Abstract: Salamanders are able to regenerate their entire limbs throughout lifespan, through a process that involves significant modulation of cellular plasticity. Limb regeneration is accompanied by the endogenous induction of cellular senescence, a state of irreversible cell cycle arrest associated with profound non‐cell‐autonomous consequences. While traditionally associated with detrimental physiological effects, here, we show that senescent cells can enhance newt limb regeneration. Through a lineage tracing approac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…Recently, p16-expressing fibroblasts were found to be a critical population for maintaining barrier integrity and tissue remodeling in the lungs (36). Senescent cells have also been shown to play a key role in limb regeneration in amphibian models (37). Deletion of these cells may compromise the barrier function of tissues and result in aberrant immune cell trafficking or leaking of certain cytokines or chemokines into the circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, p16-expressing fibroblasts were found to be a critical population for maintaining barrier integrity and tissue remodeling in the lungs (36). Senescent cells have also been shown to play a key role in limb regeneration in amphibian models (37). Deletion of these cells may compromise the barrier function of tissues and result in aberrant immune cell trafficking or leaking of certain cytokines or chemokines into the circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Efficient clearance of senescent cells has been evaluated in centenarians in response to stressors, thereby promoting tissue remodeling and regeneration. This axis of senescence-clearance-regeneration is considered essential for maintaining tissue integrity and prevention of damaged cells accumulation (Chikenji et al, 2019;Jeon et al, 2017;Walters et al, 2023). In this context, B-cell lymphoma-extra large (Bcl-Xl), an important protein involved in apoptosis control in centenarians, is further believed to play a crucial role in attenuating the senescence response.…”
Section: Cellular Senescencementioning
confidence: 99%
“…As the author suggested, these differences are explained by modifications of the molecular program that regulates the death/degeneration of muscle fibers [126]. In addition, Walters et al [128] reported the activity exhibited by senescent cells during limb regeneration in the newt. An assumption is made that the factors emitted by senescent cells activate the FGF-ERK signaling axis, thereby causing myotubules to enter the S-phase of cell cycle with production of mononuclear muscle progenitors [128].…”
Section: Regeneration Of Tissues Surrounding the Sc Of The Regenerati...mentioning
confidence: 99%
“…In addition, Walters et al [128] reported the activity exhibited by senescent cells during limb regeneration in the newt. An assumption is made that the factors emitted by senescent cells activate the FGF-ERK signaling axis, thereby causing myotubules to enter the S-phase of cell cycle with production of mononuclear muscle progenitors [128]. Thus, the issue of the source of muscle tissue regeneration in the case of appendage regeneration in salamanders is still not fully addressed [129].…”
Section: Regeneration Of Tissues Surrounding the Sc Of The Regenerati...mentioning
confidence: 99%